Effect of static electric field on the beat structures in four-wave mixing signals from semiconductor microcavities - , Suryadi; Kadoya, Yutaka; Watatani, Kenichi; Takeda, Homare; Yamanishi, Masamichi (The Physical Society of Japan, 2002)
Beat structures in the time-integrated four-wave mixing signals in semiconductor microcavities under a static electric field were investigated experimentally. We observed a significant change in the phase of the oscillation in the upper polariton mode with the change of the electric field. Through comparison with results of a theoretical analysis based on modified optical Bloch equations, the experimental results were found to strongly suggest that the exciton–exciton interaction, represented by the electric field renormalization, is significantly modified by the static electric field.